Psychic Voyages - Time-Life Books Inc.; Editor-in-Chief: Jason McManus (Alexandria, Virginia Time-Life Books, 1987)
Explores the phenomenon of near-death experiences, examining different theories on why they occur.
Include Illustrations Bibliography and Index.
Human beings are limited by the physical world, by the capacities of the body and by the earthly laws of space and time.
Keywords: Near-death experiences -- Reincarnation -- Astral projection